The effect of profitability and liquidity on stock returns: a study of food & beverage sub-sector companies listed on the Indonesia stock exchange - Nugraha, Andy Dipraja; Kusumah, R. Wedi Rusmawan (Universitas Wiralodra, 2023)
This study aims to determine the effect of profitability and liquidity on stock returns. With a sample of 30 annual reports of food & beverage sector companies listed on the Indonesia Stock Exchange (IDX) for 2019-2021, the model was selected using a purposive sampling technique. In this study, the population is 30 food & beverage sub-sector companies listed on the Indonesian stock exchange for 2019-2021. The sample passion in this study is 30 food & beverage sub-sector companies listed on the Indonesian stock exchange for 2019-2021. Furthermore, the method of data collection carried out by this study’s authors itching secondary data with literature and documentation. The collected data were analyzed using multiple linear regression analysis. Based on the study’s results, it can be concluded that (1) profitability (ROA) has a significant effect on stock returns, meaning that changes in the ups and downs of profitability will affect stock returns. (2) liquidity (CR) has a significant effect on stock returns, meaning that changes in the ups and downs of liquidity values will affect stock returns.